The origin of genos in hellenic society - Sychov, Mihkail V. (Journal of the Belarusian State University. History, 2018)
Hellenic aristocrats were divided into genes in Classical and Archaic times. It is often written in historiography, that genes had been existing since prehistoric times. This opinion is based on L. G. Morgan’s conception. But the analysis of written and archaeological sources of VIII century BC shows the following. Genes had existed only as сoncept of succession of ancestors till VIII century BC, but not as unification of people of the same generation. And exactly in VIII century BC, when the economy changed from pastoral to agricultural, the situation changed and genes became social reality.